Cloud‐Surface Coupling Alters the Morning Transition From Stable to Unstable Boundary Layer. Issue 5 (7th March 2023) - Su, Tianning; Li, Zhanqing; Zheng, Youtong
Abstract: Due to surface heating, the morning boundary layer transits from stable to neutral or convective conditions, exerting critical influences on low tropospheric thermodynamics. Low clouds closely interact with the boundary layer development, yet their interactions bear considerable uncertainties. Our study reveals that cloud‐surface coupling alters the morning transition from stable to unstable boundary layer and thus notably affects the diurnal variation of the boundary layer. Specifically, due to the reduction in surface fluxes, decoupled clouds can delay the process of eroding nocturnal inversion by 0.8‐hr and even prevent the transition of the boundary layer from happening for 12% of decoupled cases, keeping the boundary layer in a stable state during the noontime. On the other hand, when clouds are coupled with the surface, cloud‐top radiative cooling can directly cool the upper boundary layer to facilitate sub‐cloud convection, leading to an unstable boundary layer in the earlier morning. Plain Language Summary: Low clouds closely interact with the planetary boundary layer, yet their interactions bear considerable uncertainties. Our study reveals that cloud‐surface coupling plays an important role in regulating the diurnal variation of boundary layer. In particular, cloud‐surface coupling affects the energy budget of the land‐atmosphere system and further alters the transition from the stable boundary layer to the unstable boundary layer during the morning. Due to the reduction in surface fluxes, decoupled clouds can notably delay the process of eroding nocturnal inversion, keeping the boundary layer in a relatively stable state. On the other hand, when clouds are coupled with the surface, cloud‐top radiative cooling can directly cool the upper boundary layer to facilitate convection, leading to an unstable boundary layer in the earlier morning. Key Points: Decoupled clouds can notably delay the process of eroding nocturnal inversion by suppressing surface fluxes Cloud‐top radiative cooling caused by coupled clouds facilitates the formation of the unstable boundary layer in the earlier morning Cloud‐surface coupling notably affects the diurnal variation of the boundary layer by altering the phase transition of the boundary layer